PENGARUH LEVERAGE DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN (Studi Kasus Pada Perusahaan Food and beverage yang Terdaftar di Bursa Efek Indonesia Periode 2012-2016) - Aminatuz Zuhriyah; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRAK This study aims to determine the effect of Leverage and Profitability on dividend policy. Where in this research use leverage financial ratios proxied by Debt To Equity Ratio (DER) and profitability ratios earned by Return On Asset (ROA) and Return On Equity (ROE), through DER, ROA, and ROE as independent variable and DPR as the dependent variable. The sample in this research is Food and Beverage company listed in Indonesia Stock Exchange which publish its financial report period 2012-2015.11 companies that become population in this research, result of research indicate that independent variable of DER have positive effect is not significant and ROE have positive and significant influence to dependent variable of DPR, while ROA variable is removed from model because happened multicholonierity is severe. DER results that show positive means the lower the DER value then the House of Representatives dividend or dividend to the shareholders will rise and ROE results that show positive means the higher level of corporate profits then improve the company's ability to pay dividends. Keywords: Debt To Equity Ratio (DER), Return On Equity (ROA), Return On Assets (ROE) and Dividend Payout Ratio (DPR).